Detection of multiple potentially pathogenic bacteria in Matang mangrove estuaries, Malaysia - Ghadepour, Aziz; Mohd Nasori, Khairul Nazrin; Chew, Li Lee; Chong, Ving Ching; Thong, Kwai Lin; Chai, Lay Ching (Elsevier, 2014)
The deltaic estuarine system of the Matang Mangrove Forest Reserve of Malaysia is a site where several human settlements and brackish water aquaculture have been established. Here, we evaluated the level of fecal indicator bacteria (FIB) and the presence of potentially pathogenic bacteria in the surface water and sediments. Higher levels of FIB were detected at downstream sampling sites from the fishing village, indicating it as a possible source of anthropogenic pollution to the estuary. Enterococci levels in the estuarine sediments were higher than in the surface water, while total coliforms and E. coli in the estuarine sediments were not detected in all samples. Also, various types of potentially pathogenic bacteria, including Klebsiella pneumoniae, Serratia marcescens and Enterobacter cloacae were isolated. The results indicate that the Matang estuarine system is contaminated with various types of potential human bacterial pathogens which might pose a health risk to the public.